Number identification: a unique developmental pathway in mathematics?. Issue 2 (3rd March 2020) - Cramman, Helen; Gott, Sarah; Little, John; Merrell, Christine; Tymms, Peter; Copping, Lee T.
ABSTRACT: We make a prima facie case for identifying a single pathway in the learning of Hindu-Arabic numerical symbols and discuss why this ability may be a critical gateway concept in developing mathematical competencies. A representative sample of English and Scottish children was assessed using a number symbol identification paradigm in the Performance Indicators in Primary Schools (PIPS) Baseline assessment at the beginning and end of their first school year. Through a Rasch analysis of real and simulated data, we show that: (1) there appears to be a single, unidimensional pathway in learning to identify number symbols with discrete difficulty stages, (2) on examination of differential item functioning, this pathway is invariant across gender, country, socio-economic background, first language and across the first year of schooling and (3) almost all children make progress along the pathway during the year. A number identification scale may thus be a universal ruler by which all pupils could be assessed.